2022
DOI: 10.14701/ahbps.22-065
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of endoscopic retrograde cholangiopancreatography-guided gallbladder drainage compared to percutaneous cholecystostomy in acute cholecystitis

Abstract: Backgrounds/Aims: Endoscopic retrograde cholangiopancreatography-guided gallbladder drainage (ERGD) is an alternative to percutaneous cholecystostomy (PTC) for hospitalized acute cholecystitis (AC) patients. Methods: We retrospectively analyzed propensity score matched (PSM) AC hospitalizations using the National Inpatient Sample database between 2016 and 2019 to compare the outcomes of ERGD and PTC. Results: After PSM, there were 3,360 AC hospitalizations, with 48.8% undergoing PTC and 51.2% undergoing ERGD. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…Our study determined that the length of hospital stay as well as the cost incurred were higher for patients undergoing percutaneous drainage. Various other studies have concluded similar ndings [32,33].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Our study determined that the length of hospital stay as well as the cost incurred were higher for patients undergoing percutaneous drainage. Various other studies have concluded similar ndings [32,33].…”
Section: Discussionsupporting
confidence: 78%
“…Patients with co-morbidity burden were more likely to undergo percutaneous drainage rather than endoscopic drainage. Another NIS database study comparing ERCP with percutaneous drainage had similar ndings [32].…”
Section: Discussionmentioning
confidence: 79%
“…Each hospitalization was assigned a propensity score using a multivariable logistic regression, which included individual‐ (age, sex, race, and comorbidities) and hospital‐level (location, teaching status, and bed size) variables. Cases and controls were matched based on the propensity scores in a 1:1 manner within 0.01 standard deviation of the calculated score, as in prior literature 5,6 . The covariate balance was then visualized using a two‐way plot shown in Figures S1a (before the match) and S1b (after the match).…”
Section: Methodsmentioning
confidence: 99%
“…Cases and controls were matched based on the propensity scores in a 1:1 manner within 0.01 standard deviation of the calculated score, as in prior literature. 5 , 6 The covariate balance was then visualized using a two‐way plot shown in Figures S1a (before the match) and S1b (after the match). A two‐sample Wilcoxon rank‐sum (Mann–Whitney) test was used for continuous variables, and outcomes were reported with interquartile ranges (IQRs).…”
Section: Methodsmentioning
confidence: 99%
“…Matched observations had a caliper width of 0.01 for the caliper matching variable (propensity scores). Cases and controls were matched 1:1 on age, sex, and Elixhauser comorbidities, including cardiac comorbidities (heart failure and valvular dysfunction), hypertension, diabetes, and cirrhosis (compensated and decompensated), as previously reported[ 16 , 17 ]. The covariate balance was visualized using the two-way plot shown in Figure 1 .…”
Section: Methodsmentioning
confidence: 99%